Generation and evolution of interplanetary slow shocks - C.-C. Wu; S. T. Wu; M. Dryer (Annales Geophysicae)
It is well known that most MHD shocks observed within 1 AU are MHD fast shocks. Only a very limited number of MHD slow shocks are observed within 1 AU. In order to understand why there are only a few MHD slow shocks observed within 1 AU, we use a one-dimensional, time-dependent MHD code with an adaptive grid to study the generation and evolution of interplanetary slow shocks (ISS) in the solar wind. Results show that a negative, nearly square-wave perturbation will generate a pair of slow shocks (a forward and a reverse slow shock). In addition, the forward and the reverse slow shocks can pass through each other without destroying their characteristics, but the propagating speeds for both shocks are decreased. A positive, square-wave perturbation will generate both slow and fast shocks. When a forward slow shock (FSS) propagates behind a forward fast shock (FFS), the former experiences a decreasing Mach number. In addition, the FSS always disappears within a distance of 150R⊙ (where R⊙ is one solar radius) from the Sun when there is a forward fast shock (with Mach number ≥1.7) propagating in front of the FSS. In all tests that we have performed, we have not discovered that the FSS (or reverse slow shock) evolves into a FFS (or reverse fast shock). Thus, we do not confirm the FSS-FFS evolution as suggested by Whang (1987).